(untitled) (jornal of the libyan geographical society, 1997)
Rainfall is considered one of the most important climatic elements that cause desertification, as the general trend of change in its quantities, increasing and decreasing, leads to successive periods of drought and humidity every number of years, a characteristic that distinguishes all arid and semi-arid regions. In addition to that, semi-humid areas are characterized by monthly and annual changes in rainfall amounts, and fluctuations in rainfall from year to year, which leads to desertification. Desertification is one of the most important environmental problems resulting from ecological imbalance. It is a global phenomenon affecting both developing and developed countries, especially in Africa, some Asian countries, and Australia. The former Soviet Union, the United States, and Latin America, where countries such as Brazil and Chile are affected, and even the European continent has not been spared from its danger, as countries such as Greece, Spain and Portugal have been affected.